Mathematics Connection Skills of Junior High School Students in RME (Realistic Mathematics Education) Learning - Khotimah, Husnul; Hidayat, Adityawarman; Rizky, Lussy Midani (STKIP Singkawang, 2024)
Mathematics is an exact science related to numbers, numbers This research was motivated by the low mathematical connection abilities of class VII students at SMP Negeri 2 Bangkinang Kota. To overcome this problem, Realistic Mathematics Education (RME) learning.This research aims to determine the diffrences in mathematical connection abilities between student who use Realistic Mathematics Education (RME) and conventional learning. This research is a quasi-experimental study using a randomized pretest-posttest control group design. The research sample consisted of class VII F, totaling 27 students and VII G, totaling 27 students. The sampling technique used is random sampling. The data collection techniques used were observation sheets and mathematical connection ability test questions. The results of this research can be concluded that there is a difference in the average test results of students' mathematical connection abilities in the experimental class using Realistic Mathematics Education (RME) learning and the control class which applies conventional learning for class VII students at SMP Negeri 2 Bangkinang Kota. This can be proven through the Independent Sample T-Test, obtaining a sig (2-tailed) value of 0.001 < 0.05, so is rejected and Ha is accepted